Intrinsic, extrinsic and endoplasmic reticulum stress-induced apoptosis in RK13 cells infected with equine arteritis virus - Metz, German Ernesto (2016)
The modulation of the expression of caspases by viruses influences the cell survival of different cell types. Equine arteritis virus (EAV) induces apoptosis of BHK21 and Vero cell lines, but it is not known whether EAV induces apoptosis in RK13 cells, a common cell line routinely used in EAV diagnosis and research. In this study, we determined that caspase-3 expression was triggered after infection of RK13 cells with EAV in a time- and dose-dependent manner. We also detected caspase-8 and caspase-9 activation, indicating the stimulation of both extrinsic and intrinsic apoptosis pathways. Finally, we found caspase-12 activation, an indicator of endoplasmic reticulum stress-induced apoptosis. The variability observed in the apoptotic response in the different cell lines demonstrates that apoptosis depends on the distinctive sensitivity of each cell line used for investigation.